Materials and Methods for Digital Construction - (:unkn) unknown (My University, 2023)
The benefits of digital manufacturing and 3D printing technology when applied in the construction industry have proven to demonstrate considerable advantages over conventional production methods including increase in efficiency, reduced labor, ability to realize complex architecture and design optimization to effectively utilize materials characteristics and decrease production waste. For industry today, the 3D printing has emerged to address many of the needs to improve the material performance, enhance properties, and deliver complex structures with efficiency. In the case of concrete, the extension of the extrusion method to 3D (and even 4D) printings is the technological challenge that requires the modification of fresh properties of concrete and asphalt which was further explored in this research. This research reports on the extrusion of cement based compositions using a custom made 2D printer. By incorporating additional material modifiers such as polymers, fibers, and nanoparticles the fresh properties of extruded mixtures can be precisely controlled. Such mixtures can be precisely optimized to not only for the digital of 2D/3D printing and non-traditional responses such as auxetic behavior which can be tuned to perform in harsh conditions such as extreme-temperature exposures. Future research is needed to implement the developed materials and concepts in critical components of infrastructure which, in additional to mechanical loadings, undergo thermal expansion and exposed to harsh temperature environments.